Perubahan Guna Lahan Desa Karama Sebagai Dampak Aktivitas Ekonomi Masyarakat - Suriadi, Nur Adyla; Djalaluddin, Nurgadima; Aswad, Muhammad (Universitas Islam Negeri Sunan Ampel Surabaya, 2019)
The fishing settlements in Karama Village have different characteristics from other settlements because this village still maintains Mandar culture in terms of physical and non-physical aspects such as weaving lipa 'saqbe activities, fisherman cultural rituals, sandeq races, and other cultural rituals that are carried out every year. But as it develops, its existence can experience a shift. This can happen when a community's economic activities affect other cultures, either on purpose or by accident. This study aims to find out how the cultural value of the community in Karama Village has changed, especially in terms of community economic activity. It will do this by looking at land-use change, figuring out how it has changed in Karama Village because of community economic activity and coming up with policy ideas for dealing with land-use change issues in Karama Village. The study results indicate that Karama Village's administration and land use have changed. For example, 74% of the buildings have switched from residential to commercial or industrial use. Eighteen percent of buildings got more prominent because of economic activity in the neighborhood. While 28% of buildings don't add to their building area, they use their public land for business. This change has big effects on the social and economic activities mentioned in the cultural element and related to the economy or people's ways of making a living.